METHODS OF FORMING COATS WITH ANTIQUE EFFECT - Panayotov, Panayot; Georgiev, Jivko; Nikolova, Diana (Innovation in Woodworking Industry and Engineering design, 2013)
Methods of finishing for creating antique effects were analyzed. It was established that to create these finishes - chemical stains, patina powder, sealer and top-coats are used. It is easy and quick to achieve these effects, when they are formed on tannin-containing wood. It is established that antique effects can be coated on wood which doesn’t contain tannin (Spruce, Scots Pine), if the effects are made by suitable stains, paints and top-coats. It was made technologies for making „multicolored chestnut“, „antique paint“ and „crackle“ effects on chestnut and ash wood. These special effects are in use in modern fluency in furniture with antique effects. The most important qualities were explored.